An edge–cloud sparse autoencoder based cyber attack detection and measurement reconstruction for industrial cyber–physical systems - Santhi, Thulasi M.; Srinivasan, K. (Measurement : journal of the International Measurement Confederation, 2026)
•Data driven based edge-cloud approach for discriminating cyber-attack and fault.•Edge SAE is for fault identification and cloud SAE is for attack detection.•Free from system model and labelled data due to unsupervised data driven technique.•Validated effectiveness on a nonlinear simulated vehicle model and real-time system.•Overcome the computational limitation of edge server by employing trained SAE. Cyber physical systems (CPSs) are transforming industrial technology by merging physical and cyber realms resulting voluminous data and enhanced communication, but it also raises the risk of cyber attacks. However, distinguishing between malicious attacks and faults is challenging. This research proposes an innovative edge-cloud collaborative unsupervised cyber attack detection approach using two sparse autoencoders(SAEs) deployed at the edge and cloud levels. The edge-based SAE identifies faults meanwhile the cloud-based SAE detects cyber attacks. The residuals comparison accurately discerns between faults, cyber attacks and coordinated threats without relying on system models or labelled data. The method reconstructs measurements, identifies affected signals, distinguish cyber attacks from fault, and retrieves attack signals. The effectiveness of the technique is demonstrated on simulation and real-time system to promise practical application.